The bacterial spore : from molecules to systems - Driks, Adam; Eichenberger, Patrick (Professor of biology) (ASM Press, 2016)
Presents a broad-based overview of spore biology, providing in-depth coverage of both basic and applied areas of spore research. Presents the diversity of spore research and shows how these topics cohere into a unified field of knowledge. Chapters focus on important general topics as well as more specialized research areas representing the cutting edge of spore research, including broad reviews of especially important topics, such as spore molecular biology, bioremediation, issues in biodefense, and food safety.